2008
DOI: 10.1037/1072-5245.15.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Work/family demands, work flexibility, work/family conflict, and their consequences at work: A national probability sample in Taiwan.

Abstract: satisfaction and organizational commitment. It is recommended that various family-friendly company policies be reformulated taking into account core cultural values such as individualism-collectivism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
82
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 108 publications
(94 citation statements)
references
References 45 publications
9
82
0
3
Order By: Relevance
“…The significant relationships between work-family conflict and job satisfaction are consistent with the results reported by Bhuian et al [20,22,26] whereby individuals who reported higher intensities of workfamily conflict tended to experience lower levels of job satisfaction. Similar findings have also been reported by Namasivayam and Zhao [23,24,27] .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The significant relationships between work-family conflict and job satisfaction are consistent with the results reported by Bhuian et al [20,22,26] whereby individuals who reported higher intensities of workfamily conflict tended to experience lower levels of job satisfaction. Similar findings have also been reported by Namasivayam and Zhao [23,24,27] .…”
Section: Discussionsupporting
confidence: 90%
“…Relationship between work-family conflict and job satisfaction: Many researchers have demonstrated a significant negative correlation between work-family conflict and job satisfaction [20][21][22][23][24][25][26] . Similarly, in a more recent study, Yildirim and Aycan [27] reported that work-family conflict decreased employees' job satisfaction.…”
Section: H2mentioning
confidence: 99%
“…The significant direct relationships between workfamily conflict and job satisfaction are consistent with the results of previous research (Lu et al, 2008) whereby individuals who reported higher intensities of work-family conflict tended to experience lower levels of job satisfaction. Similar findings have also been reported by Namasivayam and Zhao (2007); Karatepe and Uludag (2007) and Yildirim and Aycan (2008).…”
Section: Discussionsupporting
confidence: 81%
“…Studies have shown that work-family conflict could directly decrease employees' job satisfaction (Karatepe and Uludag, 2007;Namasivayam and Zhao, 2007;Yildirim and Aycan, 2008;Lapierre et al, 2008;Lu et al, 2008). Employees experiencing work-family conflict, involving incompatible demands from work and family domains, would blame their organizations for depleting the time and energy they need for performing family roles and thus be less satisfied with their jobs.…”
Section: Introductionmentioning
confidence: 99%
“…Of the two, WFC may be especially critical. As Frone (2003) and a recent national survey of Taiwanese (Lu, Kao, Chang, Wu, & Cooper, 2008) revealed, individuals tend to experience more WFC than FWC. Thus, the present study focused specifically on WFC in comparing the results of two culturally dissimilar societies: Taiwan and the United Kingdom of Britain.…”
Section: Wfc: An Occupational Stress Perspectivementioning
confidence: 97%